The Effect Of Health Education About Exclusive Breastfeeding On The Knowledge Of Breastfeeding Mothers In Public Health Center X - Warda M; Rezqiqah Aulia Rahmat; Nurhayati Nurhayati (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Exclusive breastfeeding is the best source of nutrition for infants aged 0–6 months and plays an important role in growth, development, and improving infant immunity. However, the coverage of exclusive breastfeeding in Indonesia is still not optimal, one of the causes being the low knowledge of breastfeeding mothers. Health education is a promotive and preventive effort that can improve mothers' knowledge regarding exclusive breastfeeding. This study aims to determine the effect of health education about exclusive breastfeeding on the knowledge of breastfeeding mothers at Community Health Center X. The study used a pre -experimental design with a one-way approach. group Pretest - posttest. The sample consisted of 30 breastfeeding mothers selected using purposive sampling. The research instrument was a questionnaire on exclusive breastfeeding knowledge. Data analysis was performed using the Wilcoxon test. Signed Rank Test. The results of the study showed an increase in knowledge of breastfeeding mothers after being given health education with a p value = 0.000 (<0.05). The conclusion of this study is that health education about exclusive breastfeeding has a significant effect on increasing knowledge of breastfeeding mothers at Community Health Center X.